Risk of preeclampsia and gestational diabetes after occupational exposure to chemicals during pregnancy–A cohort study of births in Sweden 1994–2014 - Per Gustavsson; Claudia Lissåker; Maria Albin; Lars Alfredsson; Pernilla Wiebert; Håkan Tinnerberg; Karin Grahn; Lars Rylander; Jenny Selander (Environmental Research, 2025)

Nationwide multicentre study of Nanopore long-read sequencing for 16S rRNA-species identification - Sofia Brunet; Anna Grankvist; Daniel Jaen-Luchoro; Maria Bergdahl; Jean-Luc Tison; Annica Wester; Karin Elfving; Jule Brandenburg; Karolina Gullsby; Christoffer Lindsten; Lars-Ola Arvidsson; Helena Larsson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Recent improvements in Nanopore sequencing chemistry has made it a promising platform for long-read 16S rRNA sequencing. This study evaluated its clinical utility in a nationwide collaboration coordinated by Genomic Medicine Sweden. Methods Thirteen mock samples comprised of various bacterial strains and an External Quality Assessment (EQA) panel from QCMD (Quality Control for Molecular Diagnostics) were analysed by 20 microbiological laboratories across Sweden, using the recent v14 chemistry. Most laboratories generated full-length 16S rRNA sequencing libraries using an optimized protocol for the 16S Barcoding Kit 24, while two laboratories employed in-house PCR coupled with the Ligation Sequencing Kit. The commercial 16S bioinformatic pipeline from 1928 Diagnostics (1928-16S) was evaluated and compared with the open-sourced gms_16S pipeline that is based on the EMU classification tool (GMS-16S). Results Seventeen out of 20 laboratories successfully sequenced and analysed the samples. Laboratories that used sodium acetate-containing elution buffers faced compatibility issues during library construction, resulting in reduced read count. High bacterial load samples were generally well-characterized, whereas hard-to-lyse bacteria such as Gram-positive strains were detected at lower abundance . The GMS-16S tool provided improved species-level identification compared to the 1928-16S pipeline, particularly for closely related taxa within the Streptococcus and Staphylococcus genera. Conclusion Nanopore sequencing demonstrated promising potential for bacterial identification in a clinical setting. The results prompt further optimization of the protocol to improve detection of a broader range of species. This multicentre study highlights the feasibility of implementing Nanopore sequencing into clinical microbiological laboratories, for improved national precision diagnostics.

Gestational hypertension, preeclampsia, and gestational diabetes mellitus after high exposure to perfluoroalkyl substances from drinking water in Ronneby, Sweden - Matilda Ebel; Lars Rylander; Tony Fletcher; Kristina Jakobsson; Christel Nielsen (Environmental Research, 2023)

Exposure to per- and polyfluoroalkyl substances in early pregnancy and risk of cerebral palsy in children - Andreas Vilhelmsson; Lars Rylander; Anna Jöud; Christian H. Lindh; Kristina Mattsson; Zeyan Liew; Pengfei Guo; Beate Ritz; Karin Källén; Jesse D. Thacher (Science of The Total Environment, 2023)

Mild steel welding is associated with alterations in circulating levels of cancer-related proteins - Anda R. Gliga; Tahir Taj; Maria Hedmer; Eva Assarsson; Lars Rylander; Maria Albin; Karin Broberg (Archives of Toxicology, 2019)
Welding fumes were recently classified as carcinogenic to humans and worldwide millions work as welders or perform welding operations. The purpose of this study was to identify new biomarkers of welding-induced carcinogenesis. We evaluated a panel of 91 putative cancer-related proteins in serum in a cohort of welders working with mild steel ( n = 77) and controls ( n = 94) from southern Sweden sampled on two occasions 6-year apart using a longitudinal analysis (linear mixed models). The significant results from the longitudinal analysis were tested for reproducibility in welders ( n = 88) and controls ( n = 69) sampled once during the same sampling period as timepoint 1 or timepoint 2 (linear regression models), i.e., in a cross-sectional setting. The models were adjusted for age, body-mass index, and use of snus. All study participants were non-smokers at recruitment. Exposure to welding fumes was assessed using questionnaires and respirable dust measurement in the breathing zone that was adjusted for personal respiratory protection equipment. The median respirable dust in welders was 0.7 (0.2–4.2) and 0.5 (0.1–1.9) mg/m 3 at the first and second timepoints, respectively. We identified 14 cancer-related proteins that were differentially expressed in welders versus controls in the longitudinal analysis, out of which three were also differentially expressed in the cross-sectional analysis (cross-sectional group). Namely, syndecan 1 (SDC1), folate receptor 1 (FOLR1), and secreted protein acidic and cysteine rich (SPARC) were downregulated, in welders compared with controls. In addition, FOLR1 was negatively associated with years welding. Disease and function analysis indicated that the top proteins are related to lung cancer as well as cell invasion and migration. Our study indicates that moderate exposure to welding fumes is associated with changes in circulating levels of putative cancer-related proteins, out of which FOLR1 showed a clear dose–response relationship. It is, however, unclear to which extent these changes are adaptive or potential early biomarkers of cancer.

Chimney sweeps in Sweden: a questionnaire-based assessment of long-term changes in work conditions, and current eye and airway symptoms - Ayman Alhamdow; Per Gustavsson; Lars Rylander; Kristina Jakobsson; Håkan Tinnerberg; Karin Broberg (International Archives of Occupational and Environmental Health, 2017)

Determinants of maternal and fetal exposure and temporal trends of perfluorinated compounds - Amanda Ode; Lars Rylander; Christian H. Lindh; Karin Källén; Bo A. G. Jönsson; Peik Gustafsson; Per Olofsson; Sten A. Ivarsson; Anna Rignell-Hydbom (Environmental Science and Pollution Research, 2013)

Male infertility and prostate cancer risk: a nested case–control study - Yasir Ruhayel; Aleksander Giwercman; David Ulmert; Lars Rylander; Anders Bjartell; Jonas Manjer; Göran Berglund; Yvonne L. Giwercman (Cancer Causes & Control, 2010)

Incidence of hospitalized osteoporotic fractures in cohorts with high dietary intake of persistent organochlorine compounds - Ann-Kathrine Alveblom; Lars Rylander; Olof Johnell; Lars Hagmar (International Archives of Occupational and Environmental Health, 2003)

Plasma concentrations of persistent organochlorines in relation to thyrotropin and thyroid hormone levels in women - Lars Hagmar; Lars Rylander; Eva Dyremark; Eva Klasson-Wehler; Eva Marie Erfurth (International Archives of Occupational and Environmental Health, 2001)